Post-TAVR patients with atrial fibrillation: are NOACs better than VKAs?—A meta-analysis - Wang, Lu; Sang, Wanyue; Jian, Yi; Zhang, Xiaoxue; Han, Yafan; Wang, Feifei; Wang, Liang; Yang, Suxia; Wubulikasimu, Subinuer; Yang, Li; Sun, Huaxin; Li, Yaodong (Frontiers in Cardiovascular Medicine, 2023)
Objective This study aimed to compare the efficacy of novel oral anticoagulants (NOACs) with traditional anticoagulants vitamin K antagonists (VKAs) in patients with atrial fibrillation (AF) post transcatheter aortic valve replacement (TAVR). Methods Studies comparing the usage of NOACs and VKAs in AF patients with oral anticoagulant indication post-TAVR were retrieved from PubMed, EMBASE, Medline, and Cochrane databases from their building-up to Jan. 2023. The literature was screened in line of inclusion and exclusion criteria. Risk ratio (RR) or odds ratio (OR),95% confidence interval (CI) and number needed to treat (NNT) were calculated for four main indexes that composite endpoints composed mainly of any clinically relevant risk events, stroke, major bleeding, and all-cause mortality. Subsequently, a meta-analysis was performed using the RevMan5.3 and Stata 16.0 software. Results In the aggregate of thirteen studies, contained 30388 post-TAVR patients with AF, were included in this meta-analysis. Our results indicated that there was no significant difference in stroke between the NOACs group and the VKAs group, and the NOACs group had a numerically but non-significantly higher number of composite endpoint events compared with the other group. Nevertheless, the incidence of major bleeding [11.29% vs. 13.89%, RR 0.82, 95%CI (0.77,0.88), P < 0.00001, I² = 69%, NNT = 38] and all-cause mortality [14.18% vs. 17.61%, RR 0.83, 95%CI (0.79,0.88), p < 0.00001, I² = 82%, NNT = 29] were significantly lower in the NOACs group than another group. Conclusion Taken together, our data indicated that the usage of NOACs reduced the incidence of major bleeding and all-cause mortality compared to VKAs in post-TAVR patients with AF.